Impact of ongoing conflict and pathways to recovery in Sudan: Agricultural bounce-back, infrastructural investment, and social protection - Siddig, Khalid; Thurlow, James; Ahmed, Mosab O. M.; Randriamamonjy, Josee; Raouf, Mariam (International Food Policy Research Institute, 2024)
In response to the 2023 conflict in Sudan and its extensive socio-economic repercussions, this study investigates the resultant economic, poverty, and undernourishment impacts, using an economywide model for in-depth analysis at national and household levels. The study also seeks to identify effective recovery pathways that can mitigate the adverse impacts of the conflict, with a particular focus on the role of the agricultural sector. Key findings reveal significant economic contractions across all scenarios, with the GDP experiencing a reduction of up to 12% and 18% following estimates by the World Bank and the International Monetary Fund (IMF) for 2023. These estimates are included in an economywide framework, linked to a microsimulation module as major war scenarios, namely, Moderate decline & slow recovery and Sharp decline & rapid recovery, respectively. Poverty rates are projected to increase by 8 and 11.6 percentage points, affecting an additional 2.7 and 3.9 million people in the two scenarios, respectively. Undernourishment is also expected to rise significantly, with an increase of 3.9 and 6.0 percentage points, adding approximately 1.3 and 2.0 million people to those affected in the two scenarios, respectively. The analysis proposes recovery strategies that emphasize agricultural productivity, infrastructure investment, and social protection measures. By simulating enhanced agricultural productivity scenarios, the study suggests that poverty could decrease notably, with potential reductions in the poor population by as much as 1.9 million by 2028. This study underscores the urgency of coordinated policy efforts and international support to mitigate the adverse impacts of the conflict, providing a strategic roadmap for recovery initiatives aimed at sustainable development and stability in Sudan.